2012
DOI: 10.1007/s00418-012-0955-y
|View full text |Cite
|
Sign up to set email alerts
|

Gonocyte development in rats: proliferation, distribution and death revisited

Abstract: Spermatogonial stem cells are responsible for the constant production of spermatozoa. These cells differentiate from the gonocytes, but little is known about these cells and their differentiation into spermatogonia. This study analyzed rat gonocyte proliferation, death and distribution as well as their differentiation into spermatogonia. Rat testes were collected at 19 dpc and at 1, 3, 5, 8, 11 and 15 dpp and submitted to apoptosis investigation through morphological analysis and TUNEL, p53 and cleaved caspase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 42 publications
6
23
0
1
Order By: Relevance
“…Already high apoptosis levels observed at 14.5 dpp relate to the cells in the first wave of spermatogenesis. It should be mentioned that the immunocytochemistry for activated caspase 3 indicated a diffuse cytoplasmic labeling in rat gonocytes at 0.5 dpp, as observed by Zogbi et al (2012). The cytoplasm of all gonocytes at this age was labeled and a slight cytoplasmic staining could be seen until 7.5 dpp.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Already high apoptosis levels observed at 14.5 dpp relate to the cells in the first wave of spermatogenesis. It should be mentioned that the immunocytochemistry for activated caspase 3 indicated a diffuse cytoplasmic labeling in rat gonocytes at 0.5 dpp, as observed by Zogbi et al (2012). The cytoplasm of all gonocytes at this age was labeled and a slight cytoplasmic staining could be seen until 7.5 dpp.…”
Section: Discussionmentioning
confidence: 57%
“…3D and E). The presence of activated caspase 3 in these cells can be explained by the fact that it is involved not only in the cell death system but also in the self-renewal and Gonocyte neonatal development following MO differentiation processes of germ cells (Fujita et al 2008, Zogbi et al 2012. According to Dejosez et al (2008), caspase 3 also recognizes critical pluripotency factors for embryonic stem cell function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The study of the index started from the 60th day of postnatal ontogenesis, as the migration of monoblasts and the first wave of spermatogenesis are over by this time. 16 This indicator, as the analysis showed, was of high level (3.32 ± 0.15), that is obviously related to the transition to the full-fledged spermatogenesis process, culminating in the formation of spermatozoa.…”
Section: Discussionmentioning
confidence: 98%
“…16 The formation of the first spermatogonia dates back to 3e6 day of 17 The analysis of the total content of spermatogenous cells in seminiferous convoluted tubules showed that spermatozoa, mature male sex cells, have a greater representativeness among all the spermatogenous cells in testes of experimental animals at the age of 2 months of postnatal development. Male stem cells, spermatogonia, take the second place in quantitative terms.…”
Section: Discussionmentioning
confidence: 99%